(untitled) (Revista Iberoamericana de Bioética, 2017)
In the implementation of heterologous assisted reproduction procedures, the donation of supernumerary embryos is a constant in current regulation. In Mexico, the State of Queretaro is unique in how it regulates this legal act, so important for relationships sustained under current family law: it allows infertile couples the opportunity to adopt supernumerary embryos. This paper analyses two essential aspects: the child’s right to know their genetic origin and the implicit prohibition of prenatal and preimplantation genetic diagnosis, giving rise to various legal implications.